Pregnancy and phaeochromocytoma/paraganglioma: clinical clues affecting diagnosis and outcome – a systematic review. (25th January 2021) - Langton, K; Tufton, N; Akker, S; Deinum, J; Eisenhofer, G; Timmers, HJLM; Spaanderman, MEA; Lenders, JWM
Abstract : Background: Phaeochromocytoma and paraganglioma (PPGL) in pregnancy, if not diagnosed antepartum, pose a high risk for mother and child. Objective: To examine the clinical clues of antepartum and postpartum/postmortem diagnosis of PPGL. Search strategy: Case reports on PPGL in pregnancy published between 1 January 1988 and 30 June 2019 in English, German, Dutch or French. Selection criteria: Case reports containing a predefined minimum of clinical data on PPGL and pregnancy. Data collection and analysis: Two authors independently performed data extraction and assessed data quality. We calculated odds ratios (OR) (with 95% confidence intervals) and used uni‐ and multivariable logistic regression analysis. Main results: Maternal and fetal/neonatal mortalities were 9.0% (18/200) and 14.2% (29/204), respectively. Maternal mortality was 42‐fold higher with PPGL diagnosed postpartum/postmortem (17/58; 29.3%) than antepartum (1/142; 0.7%) (adjusted OR 45.9, 95% CI 5.67–370, P  = 0.0003). Offspring mortality was 2.6‐fold higher with PPGL diagnosed postpartum/postmortem than antepartum (OR 3.1, 95% CI 1.38–6.91, P  = 0.0044). Hypertension at admission (OR 2.29, 95% CI 1.12–4.68, P  = 0.022), sweating (OR 3.14, 95% CI 1.29–7.63, P  = 0.014) and a history of PPGL, a known PPGL‐associated gene mutation or adrenal mass (OR 8.87, 95% CI 1.89–41.64, P  = 0.0056) were independent factors of antepartum diagnosis. Acute onset of symptoms (OR 8.49, 95% CI 3.52–20.5, P  < 0.0001), initial diagnosis of pre‐eclampsia (OR 6.34, 95% CI 2.60–15.5, P  < 0.0001), admission for obstetric care (OR 10.71, 95% CI 2.70–42.45, P  = 0.0007) and maternal tachycardia (OR 2.72, 95% CI 1.26–5.85, P  = 0.011) were independent factors of postpartum diagnosis. Conclusion: Several clinical clues can assist clinicians in considering an antenatal diagnosis of PPGL in pregnancy, thus potentially improving outcome. Tweetable abstract: Systematic review of 204 pregnant patients with phaeochromocytoma identified clinical clues for a timely antepartum diagnosis. Tweetable abstract: Systematic review of 204 pregnant patients with phaeochromocytoma identified clinical clues for a timely antepartum diagnosis.